{Exercise and Sedentary Habits Among Adolescents with PCOS} - Eleftheriadou, M.; Michala, L.; Stefanidis, K.; Iliadis, I.; Lykeridou, A.; Antsaklis, A. (Journal of Pediatric and Adolescent Gynecology, 2012)
Study Objective: The purpose of this study was the recording of physical activity and sedentary habits of adolescents with polycystic ovarian syndrome (PCOS). Methods: We performed a structured interview to assess the level of physical activity and sedentary habits of girls with PCOS. We used a group of healthy adolescents as controls. All girls had their age, height, weight, hip and waist circumference measured and their BMI calculated. Results: 81 girls (35 with PCOS and 46 controls) participated in the study. Girls with PCOS engaged in physical activities less than controls. Even when they did, the frequency and intensity of exercise was less. Also, girls with PCOS were less likely to be aware of the positive effects of exercise on their health. Girls in both groups were sedentary in excess of the 4 hours per day limit, which has been linked with obesity. Conclusion: Healthy teenagers were involved in a sporting activity more often and more frequently than the PCOS group. Athletic and sedentary habits of adolescents with PCOS may interact with other factors leading to obesity. © 2012 North American Society for Pediatric and Adolescent Gynecology.
Keywords: adolescence; PCOS; Sedentary habits; Sporting activity